A Comprehensive Review of n-butylidenephthalide: The Potential Therapeutic Effect and Possibility for Targeted Therapy - Swati; Sarma, Kangkan; Bhardwaj, Ruchi; Chauhan, Laxita; Sharma, Ritika; Mal, Payel (Natural Products Journal, The, 2025)
n-Butylidene phthalide (N-BP) is a natural derivative obtained from the chloroform extract of Angelica Sinensis. In conventional medicine, it treats different ailments. Various pharmacological properties are associated with it, including anticancer, anti-inflammatory, and neuroprotective properties. Based on its reported pharmacokinetic profile, n-BP has low oral bioavailability and is rapidly absorbed and eliminated from the body. The compound has diverse pharmacological effects with lower stability, bioavailability, rapid absorption, and elimination. Furthermore, a targeted drug delivery system using a nanocarrier can improve pharmacokinetic-molecular profiling, specificity, efficacy, personal approach, and drug resistance. This review summarizes and emphasizes the pharmacokinetics, and pharmacology of n-butylidene phthalide, and the molecular targeting approach to treat cancer, inflammation, Parkinsonism, excitotoxicity, and Alzheimer’s.
Keywords: pharmacokinetic